2021
DOI: 10.3389/fnagi.2021.766884
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Gait Signatures of Post-stroke Dementia With Toe-Off and Heel-to-Ground Angles Discriminate From Alzheimer’s Disease

Abstract: Given the limited power of neuropsychological tests, there is a need for a simple, reliable means, such as gait, to identify mild dementia and its subtypes. However, gait characteristics of patients with post-stroke dementia (PSD) and Alzheimer’s disease (AD) are unclear. We sought to describe their gait signatures and to explore gait parameters distinguishing PSD from post-stroke non-dementia (PSND) and patients with AD. We divided 3-month post-stroke patients into PSND and PSD groups based on the Mini-Mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Gait Pace and Rhythm accounted for the majority of variance in daily life mobility. The metrics within these domains, including gait speed, heel-strike angle, and toe-off angle, have been linked to fatigue and muscle weakness in populations with neurological diseases, 30,31,52 but this is the rst evidence that these mobility characteristics associate with worse clinical outcomes in prostate cancer survivors on ADT. Fatigue and deconditioning also contribute to low self-report activity levels in patients on ADT, and we observed fewer daily bouts and shorter bout length in participants in our sample who reported more falls, were frailer, and had lower functioning than participants with higher Activity scores.…”
Section: Discussionmentioning
confidence: 95%
“…Gait Pace and Rhythm accounted for the majority of variance in daily life mobility. The metrics within these domains, including gait speed, heel-strike angle, and toe-off angle, have been linked to fatigue and muscle weakness in populations with neurological diseases, 30,31,52 but this is the rst evidence that these mobility characteristics associate with worse clinical outcomes in prostate cancer survivors on ADT. Fatigue and deconditioning also contribute to low self-report activity levels in patients on ADT, and we observed fewer daily bouts and shorter bout length in participants in our sample who reported more falls, were frailer, and had lower functioning than participants with higher Activity scores.…”
Section: Discussionmentioning
confidence: 95%
“…Based on a previous study in Italy on people with and without PD, alterations in gait ratio were expected; Peppe et al [ 27 ] suggested that compared with healthy participants, patients with PD have prolonged stance phases (patients with PD: 68.1% vs patients without PD: 63.6%; P <.001) [ 27 ]. Another study in 31 patients older than 55 years in China [ 46 ] investigated the relationship between gait characteristics and dementia, such as poststroke dementia (PSD) and AD. Ni et al [ 46 ] showed that in all gait tests, the percentage of time spent in the stance phase was longer (patients with PSD: 63.95% vs patients with AD: 63.09% vs healthy adults: 62.15%; P =.002) and in the swing phase was shorter (patients with PSD: 36.04% vs patients with AD: 36.91% vs healthy adults: 37.86%; P =.002) among patients with dementia than among healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in 31 patients older than 55 years in China [ 46 ] investigated the relationship between gait characteristics and dementia, such as poststroke dementia (PSD) and AD. Ni et al [ 46 ] showed that in all gait tests, the percentage of time spent in the stance phase was longer (patients with PSD: 63.95% vs patients with AD: 63.09% vs healthy adults: 62.15%; P =.002) and in the swing phase was shorter (patients with PSD: 36.04% vs patients with AD: 36.91% vs healthy adults: 37.86%; P =.002) among patients with dementia than among healthy controls. Taken together, these studies highlight that older individuals with gait imbalance are relatively susceptible to a decrease in cognitive function.…”
Section: Discussionmentioning
confidence: 99%